2009
DOI: 10.1007/s11481-009-9160-8
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine-Induced Behavioral Sensitization Is Enhanced in the HIV-1 Transgenic Rat

Abstract: Methamphetamine (METH) addiction is prevalent among individuals with HIV infection. We hypothesize that HIV-positive individuals are more prone to METH use and to the development of METH dependence. To test this hypothesis, we examined the effects of METH (daily intraperitoneal injection 2.5 mg/kg for 6 days) on rearing and head movement in 12-13-week-old male HIV-1 transgenic (HIV-1Tg) rats compared to F344 control rats as an indicator of behavioral sensitization, also representing neural adaptation underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…They found that METH induced an increase in body temperature, rearing, and stereotypical head movement over days (behavioral sensitization) in both the HIV-1Tg and F344 rats, but with greater changes occurring in HIV-1Tg rats. METH attenuated the expression of the DA receptor, D1R, in the PFC of the HIV-1Tg rats, but not in the F344 rats (Liu et al, 2009). In another study, HIV-1Tg rats were shown to be more prone to both the behavioral sensitization and acute physiological effects (hyperthermia) of METH than the control rats (Kass, Liu, Vigorito, Chang, & Chang, 2010).…”
Section: Methamphetamine and Hiv-1mentioning
confidence: 93%
See 3 more Smart Citations
“…They found that METH induced an increase in body temperature, rearing, and stereotypical head movement over days (behavioral sensitization) in both the HIV-1Tg and F344 rats, but with greater changes occurring in HIV-1Tg rats. METH attenuated the expression of the DA receptor, D1R, in the PFC of the HIV-1Tg rats, but not in the F344 rats (Liu et al, 2009). In another study, HIV-1Tg rats were shown to be more prone to both the behavioral sensitization and acute physiological effects (hyperthermia) of METH than the control rats (Kass, Liu, Vigorito, Chang, & Chang, 2010).…”
Section: Methamphetamine and Hiv-1mentioning
confidence: 93%
“…In summary, the presence of HIV-1 viral proteins leads to a decrease in DA receptors (Liu et al, 2009) and may explain the behavioral evidence that indicates that HIV-1Tg rats are more prone to addiction (Chang & Connaghan, 2012;.…”
Section: Hiv-1 and The Dopaminergic Systemmentioning
confidence: 97%
See 2 more Smart Citations
“…Tat transgenic mice exhibit increased DA transporter expression (Perry et al, 2010). HIV-1 transgenic rats show enhanced behavioral sensitization to methamphetamine (Liu et al, 2009; Kass et al, 2010) but attenuated nicotine-mediated behavioral sensitization (Midde et al, 2011). These studies suggest that HIV-1 viral proteins alter dopaminergic pathways that in part, mediate behavioral sensitization.…”
Section: Introductionmentioning
confidence: 99%